Visiting Tourism Destination: Is It Influenced by Smart Tourism Technology? - Eko Susanto; Syifaa Novianti; Wahyu Rafdinal; Mega Fitriani Adiwarna Prawira; Chandra Budi Septyandi (Program Pascasarjana, 2020)
The development of technology has changed various sectors in life to be smart, including tourism. This study aims to analyze the effect of smart tourism technology attributes on visit intention and visiting tourist destinations. This study used a sample of 324 tourists in West Java Province, Indonesia. Partial Least Square is applied to test the relationship between variables. The results of the study revealed that smart tourism technology attributes such as smart information systems, smart tourism management, smart sightseeing, e-commerce systems, smart safety, smart traffic, and virtual tourism objects affect visit intention. The study also revealed the effect of visiting intentions on visits to tourist destinations. The findings of this study provide the basis for formulating strategies for implementing smart tourism technology that is appropriate in attracting tourist visits.Keywords: Smart tourism technology, Tourism destination, Tourist behavior, Visit intention.